An alternating current heating method for lithium‐ion batteries from subzero temperatures. (27th June 2016) - Zhu, Jiangong; Sun, Zechang; Wei, Xuezhe; Dai, Haifeng
SummAry: An alternating current (AC) heating method for lithium‐ion batteries is proposed in the paper. Effects of current frequency, amplitudes and waveforms on the temperature evolution and battery performance degradation are respectively investigated. First, a thermal model is established to depict the heat generation rate and temperature status, whose parameters are calibrated from the AC impedance measurements under different current amplitudes and considering battery safe operating voltage limits. Further experiments with different current amplitudes, frequencies and waveforms on the 18650 batteries are conducted to validate the effectiveness of the AC heating. The experimental data recorded by appropriate measurement instrument are of great consistence with simulation results from the thermal model. At high frequency, the temperature rises prominently as the current increases, and high frequency serves as a good innovation to reduce the battery degradation. However, efficient temperature rise can be obtained from high impedance at low frequencies. Typically, 600 s is needed to heat up the battery from −24 °C to 7.79 °C with sinusoidal waveform and approximately from −24 °C to 25.6 °C with rectangular pulse waveform at 10A and 30 Hz. The model and experiments presented have shown potential value in battery thermal management studies for electric vehicle (EV)/hybrid electric vehicle (HEV) applications at subzero temperatures. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : An alternating current (AC) heating method for lithium‐ion batteries is proposed. A thermal model is established to depict the heat generation rate and temperature, and model is calibrated considering voltage limit and impedance under different current. Experiments are conducted to validate the effectiveness of the AC heating, and the effects of current frequency, amplitudes and current waveforms are also investigated.